Chemical looping technologies for carbon capture and energy conversion - Saqline, Syed (Nanyang Technological University, 2023)
This Thesis is concerned with chemical looping technologies for carbon capture and energy conversion of fossil fuels. In chemical looping, solid oxygen carriers are cyclically reduced and oxidised to aid reactions such as combustion, air separation, thermochemical splitting etc. Chemical looping combustion has been proven to be a cost-competitive solution for producing low carbon electricity. The caveat to advance this technology lies in the further improvements in efficiency and development of carriers with efficient oxygen release capacity. The research in this Thesis has three major directions aimed at developing chemical looping technologies: (a) to develop realistic models of CLC powerplants with advanced steam cycles, (b) to model novel chemical looping coupled supercritical CO2 cycles for ultrahigh efficiency power generation, and (c) to synthesise and test novel synthetic ternary oxides phase of ferrites in chemical looping CO2 capture and oxygen release. The coupling of chemical looping combustion of solid fuels with advanced steam-based power cycles, viz. supercritical, ultra-supercritical and advanced ultra-supercritical Rankine cycles was investigated in Chapter 4. The energy and exergy efficiencies of the various chemical looping combustion power plant configurations are compared against the reference plants without carbon capture. This work incorporates practical considerations for reactor design. With an upper operating temperature limit of 950 °C, the maximum efficiencies achievable by integrated gasification combined cycle chemical looping combustion (IGCC–CLC) and in situ gasification chemical looping combustion power plants (iG-CLC) are 41.3% and 41.5%, respectively. Overall, iG-CLC emerges as the most efficient CLC configuration. Comparing to an integrated gasification combined cycle without carbon capture, the energy efficiency penalties for capturing CO2 from iG-CLC coupled with subcritical, supercritical, ultra-supercritical or advanced ultra-supercritical steam cycles are 5.1%, 5.0%, 5.2% or 13.0%, respectively. The biomass-fired chemical looping combustion power plants also show low energy efficiency penalties (<2.5%) compared to the reference biomass power plants without CO2 capture. The modelling results suggest that chemical looping combustion will remain an attractive carbon capture technology for solid fuel power plants, in a future when supercritical steam turbines become the norm. Chapter 5 proposes a novel power cycle coupling the Allam cycle, which is a class of oxy-fuel combustion power cycles using supercritical CO2 (s-CO2) as the thermal fluid, with chemical looping air separation (CLAS) to achieve power generation with inherent capture of CO2. Compared to other conventional CO2 capture techniques, the Allam cycle stands out owing to its high fuel-to-electricity conversion efficiency (~55-59%), the elimination of the Rankine cycle and reduced physical footprint. A key source of energy penalty of Allam cycle comes from the air separation unit (ASU), which supplies pure oxygen via an energy intensive cryogenic process. The integration of CLAS system with the Allam cycle show that the Allam-chemical looping air separation (Allam-CLAS) process can achieve 56.04% net electrical efficiency with a 100% CO2 capture rate, when a Co3O4-based oxygen carrier is used. This is about 6% efficiency points higher than the Allam cycle coupled to a cryogenic ASU. The exergetic efficiency of the Allam-CLAS system driven by the Co3O4-CoO redox cycle is 57.13%, also more favourable than a conventional Allam-ASU system (with reported exergetic efficiency of 53.4%). The newly proposed Allam-CLAS power cycle in this thesis presents a highly efficient, and cost-competitive solution to generate zero-carbon electricity from natural gas. The performance of the oxygen carriers is vital to the overall CLC plant. It is also of utmost importance to develop oxygen carriers with multifunctional characteristics and high oxygen release capacities. In Chapter 6, the performance of two ternary oxides – Ba3Fe2O6 and Ba5Fe2O8 were investigated for chemical looping oxygen release and carbon dioxide capture. The structures of both barium ferrites were characterised because the relevant structural information is lacking in the literature. Temperature swing experiments in a TGA showed that Ba3Fe2O6 exhibits excellent recyclability and satisfactory chemical looping oxygen uncoupling (CLOU) activity. Reversible oxygen release and uptake was observed over temperature swing cycles between 550 and 950 °C. In comparison, Ba5Fe2O8 was less active for CLOU. On the other hand, Ba5Fe2O8 showed excellent performance in reversibly taking up CO2, with a CO2 capture capacity of ~7 wt% consistently over multiple CO2 capture cycles at 1000 °C. The evolution of the phase compositions of the two barium ferrites during CLOU and CO2 capture cycles was studied by in situ XRD at high temperatures in reactive gas environments. In summary, the work presented in this thesis has offered advancements to chemical looping technologies in the context of designing, optimising and understanding novel chemical looping processes and exploration of novel materials for chemical looping applications.